PENGARUH E-BOOK INTERAKTIF BERBASIS CANVA TERHADAP HASIL BELAJAR SISWA MATERI SISTEM PENCERNAAN MANUSIA PADA SISWA KELAS V DI SD NEGERI 1 TARAJU - Endang Yuda Nuryenda; Idad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the effect of Canva-based interactive e-books on fifth-grade students' learning outcomes in the human digestive system at SD Negeri 1 Taraju. In an increasingly complex educational context, interactive e-books are expected to increase students' interest and understanding of abstract scientific concepts. Using quantitative methods and a one-group pretest-posttest design, the study involved 30 students who were tested before and after the e-book implementation. Data collection was carried out through tests consisting of a pretest, treatment, and posttest. The results of the analysis showed a significant increase, with an average pretest score of 62 and a posttest score of 85, and a significance value (sig.) of 0.000 which is lower than the significance level of 0.05, which causes the null hypothesis to be rejected and the alternative hypothesis to be accepted. Adjusted R Square 75.7% indicates that the use of e-books contributes significantly to improving student learning outcomes. This study recommends that teachers consider the use of interactive e-books in learning to improve learning outcomes, as well as encourage further research on innovative learning media.